Singapore's regional health systems—a data‐driven perspective on frequent admitters and cross utilization of healthcare services in three systems. (29th June 2015) - Saxena, Nakul; You, Alex Xiaobin; Zhu, Zhecheng; Sun, Yan; George, Pradeep Paul; Teow, Kiok Liang; Chong, Phui‐Nah; Sim, Joe; Wong, John Eu Li; Ong, Benjamin; Foo, Hee Jug; Soh, Eugene Fidelis; et al.
Summary: Introduction: With population health management being a priority in the Singapore, this paper aims to provide a data‐driven perspective of the population health management initiatives to aid program planning and serves as a baseline for evaluation of future implemented programs. Methods: A database with information on patient demographics, health services utilization, cost, diagnoses and chronic disease information from 2008 to 2013 for three regional health systems in Singapore was used for analysis. Patients with three or more inpatient admissions were considered as "Frequent Admitters." Health service utilization was quantified, and cross utilization of services was studied. One‐year readmission rate for inpatients was studied, and a predictive model for readmission or death was developed. Results: There were a total of 2.8 M patients in the database. Frequent admitters accounted for 0.9% of all patients with an average cost per patient of S29 547. Of these, 89% had chronic diseases. Cross utilization of health services showed that 8.2% of the patients utilized services from more than one hospital with 19.6% utilizing hospital and polyclinic services in 2013. The highest risk of readmission or death was for those patients who had five or more inpatient episodes in each of the preceding 2 years. Conclusion: By understanding the profile of the patients and their utilization patterns in the three regional health systems, our study will help clinicians and decision makers design appropriate integrated care programs for patients with the aim of covering the healthcare needs for the enitre population across the healthcare spectrum in Singapore. Copyright © 2015 John Wiley & Sons, Ltd.